Performance Assessment of Sharia Commercial Banks in Indonesia based on Sharia Maqashid Index (Case Study on Three Selected Banks 2015-2021) - Aulia Rahmawati Zulfa; Ruhadi Ruhadi; Kristianingsih Kristianingsih (Journal of Applied Islamic Economics and Finance, 2022)
This purpose of this study was to determine the performance of selected Islamic commercial banks in Indonesia using the Maqashid Syariah Index. The type of data used is secondary data obtained from the financial statements of each sample of Islamic commercial banks, namely Bank Muamalat, BCA Syariah, and BJB Syariah during the 2015-2021 periods. This research is a descriptive quantitative research using descriptive statistical analysis and the Simple Additive Weighting method. The results of this study are that BCA Syariah has the highest sharia maqashid index measurement results (39,56%) when compared to Bank Muamalat (38,40%) and BJB Syariah (35,58%). From the calculation results, there are no Islamic commercial banks that can consistently achieve high scores on each performance ratio assessment.